Comparison of the Fruit Volatile Profiles of Five Muscadine Grape Cultivars (Vitis rotundifolia Michx.) Using HS-SPME-GC/MS Combined With Multivariate Statistical Analysis - Deng, Honghong; He, Runmei; Long, Meicun; Li, Yanmei; Zheng, Yuanyuan; Lin, Lijin; Liang, Dong; Zhang, Xiaoai; Liao, Ming'an; Lv, Xiulan; Deng, Qunxian; Xia, Hui (Frontiers in Plant Science, 2021)
Fruit aromas are composed of a complex mixture of volatile organic compounds, which are essential attributes associated with the overall flavor and consumer preference. Muscadine grape (Vitis rotundifolia Michx., MG) is an aroma-dense fruit crop. However, there is very scarce information on its volatile profiles. In this study, the volatile constituents of five newly introduced MG cultivars, including Alachua, Carlos, Fry, Granny Val, and Noble, were profiled using headspace solid-phase microextraction-gas chromatography-mass spectrometry combined with multivariate statistical analysis. A total of 44 compounds, including esters, aldehydes, alcohols, fatty acids, terpenes, ketones, and furan, were identified and relatively quantified. Principal component analysis and partial least-squares discriminate analysis clearly discriminated the five MG cultivars on the basis of their volatile profiles. The specific volatiles that contributed the most to this discrimination were highlighted. Geraniol and cinnamyl alcohol were demonstrated to be essential for characterizing the Alachua MG cultivar, whereas ethyl trans-2-butenoate and propyl acetate were shown to be important compounds to characterize the Noble MG cultivar. 2-Ethyl-1-hexanol, (Z)-3-hexenal, and (E)-2-hexenol were closely related to the Carlos, Fry, and Granny Val cultivars, respectively. This investigation is the first in-depth exploration of the volatile profiles of the aroma-dense muscadine grape, which is essential for future genetic or biotechnological improvements to attain a cultivar with the desired flavor.